(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
In coworkings, one of the behaviors involved in social interactions is cooperation. This can be defined as the interrelated behavior between members of a group producing consequences common to the group, with benefits for each individual. This study aimed to program and implement an intervention to establish the practice of cooperation in coworking, in Londrina city. Eight professionals participated. A questionnaire and the Repeated Prisoner’s Dilemma game measured cooperation, before and after the intervention, in a group design. In the intervention, participants in the experimental group were proposed to plan a cooperative project. The results showed that, in the game, the experimental group had a more robust increase when compared to itself (increase of 59% for the EG and 13% for the CG), and the EG increased 27% when compared with the CG, which suggests that intervention may have been the variable that favored cooperative choices.